Sweet tooth. [4], Endangered species - Lemire, Jeff (Vertigo, 2012)
"They were hunted...but they survived. The half-animal hybrid child called Gus and the big man called Jepperd have escaped the clutches of a brutal militia, with a ragtag band of scientists, survivors, and other hybrids in tow. Though the betrayals and sins of the past are fresh in their minds, an uneasy truce binds the group together. Now they head north to Alaska, where salvation from the sickness that slaughtered billions--and the mysterious condition that created Gus and his hybrid friends--may be found."--P. [4] of cover.